Insoluble Aβ overexpression in an App knock-in mouse model alters microstructure and gamma oscillations in the prefrontal cortex, affecting anxiety-related behaviours - Eleftheria Pervolaraki; Stephen P. Hall; Denise Foresteire; Takashi Saito; Takaomi C. Saido; Miles A. Whittington; Colin Lever; James Dachtler (The Company of Biologists, 2019)
We studied a new amyloid-beta precursor protein (App) knock-in mouse model of Alzheimer's disease (AppNL-G-F), containing the Swedish KM670/671NL mutation, the Iberian I716F mutation and the Artic E693G mutation, which generates elevated levels of amyloid beta (Aβ)40 and Aβ42 without the confounds associated with APP overexpression. This enabled us to assess changes in anxiety-related and social behaviours, and neural alterations potentially underlying such changes, driven specifically by Aβ accumulation. AppNL-G-F knock-in mice exhibited subtle deficits in tasks assessing social olfaction, but not in social motivation tasks. In anxiety-assessing tasks, AppNL-G-F knock-in mice exhibited: (1) increased thigmotaxis in the open field (OF), yet; (2) reduced closed-arm, and increased open-arm, time in the elevated plus maze (EPM). Their ostensibly anxiogenic OF profile, yet ostensibly anxiolytic EPM profile, could hint at altered cortical mechanisms affecting decision-making (e.g. 'disinhibition'), rather than simple core deficits in emotional motivation. Consistent with this possibility, alterations in microstructure, glutamatergic-dependent gamma oscillations and glutamatergic gene expression were all observed in the prefrontal cortex, but not the amygdala, of AppNL-G-F knock-in mice. Thus, insoluble Aβ overexpression drives prefrontal cortical alterations, potentially underlying changes in social and anxiety-related behavioural tasks. This article has an associated First Person interview with the first author of the paper.